PENGARUH IMPLEMENTASI GREEN ACCOUNTING, CORPORATE SOCIAL RESPONSIBILITY (CSR) DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN SEKTOR BASIC MATERIALS YANG TERDAFTAR DI BURSA EFEK INDONESIA - Nafisah Nurulrahmatiah; Aris Munandar (Nusantara Hasana Journal, 2025)
Rapid industrial growth is often accompanied by increased energy consumption, material use, and greater environmental impact. Pollution issues and global demands for sustainable business encourage companies to implement more environmentally friendly and socially responsible business practices. This is done not only as a form of corporate social responsibility but also as a way to build a corporate image and thereby increase company value. This study aims to determine the effect of green accounting, CSR, and profitability on the value of basic material companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. This study uses associative analysis with a quantitative approach. The study population is all 22 basic material companies listed on the IDX. The sample size is 9 basic material companies listed on the IDX for the 2019-2023 period. The sampling technique used is purposive sampling. Data collection techniques include documentation and literature review. This study used classical assumptions, multiple linear regression, correlation and determination coefficients, and t-tests or partial tests using SPSS version 23. Statistical test results indicate that CSR influences company value, while green accounting and profitability have no effect on the value of basic material companies listed on the IDX for the 2019-2023 period.